(untitled) (Fiep Bulletin - online, 2014)
This article has as objective to appraise aquatic, nautical and maritime sports understanding the limits between each one. Also it intends to show a historical panorama of the practised aquatic sports in the Espirito Santo. This qualitative, descriptive research, of bibliographical character was used of books, articles of periodicals, magazines and works of conclusion of course for the collection of data. References as Marinho (s.d), Capinussu (1979) amongst others had been permanent and necessary consultations. The results have presented easied use of terms as aquatic, nautical and maritime associating them it one same environment for times becoming maken a mistake. Also it has a variety of aquatic sports practised in the State showing the difficulty for spreading, training and accompaniment for qualified professionals mainly when we detect that in the courses of formation of professors few exist or no reference to these modalities. The security in the practical one of these sports reveals deficit, with little use of the basic principles of security. We recommend that more specific studies are made in the area of aquatic sports, therefore the person from de State of Espirito Santo reality is not differentiated of the majority of the Brazilian states.